An update on fecal microbiota transplantation for the treatment of gastrointestinal diseases. Issue 2 (12th November 2021) - Waller, Karen M. J.; Leong, Rupert W.; Paramsothy, Sudarshan
Abstract: Our understanding of the microbiome and its implications for human health and disease continues to develop. Fecal microbiota transplantation (FMT) is now an established treatment for recurrent Clostridioides difficile infection. There is also increasing evidence for the efficacy of FMT in inducing remission for mild–moderate ulcerative colitis. However, for other indications, data for FMT are limited, with randomized controlled trials rare, typically small and often conflicting. Studies are continuing to explore the role of FMT for many other conditions, including Crohn's disease, functional gut disorders, metabolic syndrome, modulating responses to chemotherapy, eradication of multidrug resistant organisms, and the gut–brain axis. In light of safety, logistical, and regulatory challenges, there is a move to standardized products including narrow spectrum consortia. However, the mechanisms underpinning FMT remain incompletely understood, including the role of non‐bacterial components, which may limit success of novel microbial approaches.